How safe and effective is stentless laparoscopic ureterolithotomy in elderly patients?. Issue 8 (13th May 2021) - Aydin, Cemil; Akkoc, Ali; Aydin, Zeynep Banu
Abstract: Purpose: With the improvement of minimally invasive urology procedures, open surgical interventions are less common to treat ureteral calculus. Laparoscopic ureterolithotomy (LU) indications are large multiple and/or impacted ureteral calculus that may not be treated with shock‐wave lithotripsy or ureterorenoscopy approaches. The aim of our study was to investigate the feasibility and safety of stentless LU in elderly patients. Methods: Between October 2011 and December 2019, 38 geriatric patients underwent stentless transperitoneal LU for upper/mid ureteral calculi. The transperitoneal route was applied in all patients by two surgeons. No double J stent inserted in any patient. The data of all patients reviewed retrospectively. Results: The average age was 64.60 ± 3.70 years. The mean calculi size was 19.42 ± 1.41 mm. Ten patients had unsuccessful shock wave lithotripsy or ureterorenoscopy history. The calculi‐free rate was 100%. Clavien grade 1 complications were seen in 11 (28.9%) cases. No major perioperative and postoperative complications were encountered. The average length of hospital stay was 3.24 ± 1.53 days. Conclusion: The significant advances in medical technology and healthcare, lead a rising number of geriatric patients to take benefit of even complicated surgery. Although laparoscopy and its safety in the geriatric population pursues a challenge and the assessment of this procedure is hence obligatory, we think that stentless LU is safe, economical and less uncomfortable for elderly patients.